2006
DOI: 10.1002/pssb.200672554
|View full text |Cite
|
Sign up to set email alerts
|

On the ductile response dependence upon phase transformation in diamond turning of semiconductors

Abstract: It is well established that during machining, materials with lower hardness presents higher ductility. However, in the machining of semiconductor crystals the brittle to ductile transition may not strictly follow this rule. This paper intends to show that the extent of the ductile response of monocrystalline semiconductors can not be related to its microhardness value, since the plastic behavior of semiconductor crystals is related to a phase transformation induced by pressure/stress. This was investigated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Moreover, to date, little work has been carried out to investigate the relationship between anisotropy of silicon crystal and phase transformation during micromachining. In addition, as mentioned earlier, the indentation and diamond-turning studies suggested different ductile responses when a difference between microhardness and transition pressure value is present [8,23]. It has been shown that when the values of indentation hardness and the critical transition pressure are close, as in the case of silicon, the ordinary diamond-cubic silicon transforms to the denser b-tin structure under hydrostatic pressure at room temperature, and the ductile mode is the main material removal mechanism during machining.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, to date, little work has been carried out to investigate the relationship between anisotropy of silicon crystal and phase transformation during micromachining. In addition, as mentioned earlier, the indentation and diamond-turning studies suggested different ductile responses when a difference between microhardness and transition pressure value is present [8,23]. It has been shown that when the values of indentation hardness and the critical transition pressure are close, as in the case of silicon, the ordinary diamond-cubic silicon transforms to the denser b-tin structure under hydrostatic pressure at room temperature, and the ductile mode is the main material removal mechanism during machining.…”
Section: Introductionmentioning
confidence: 69%
“…The phase transition for GaAs is estimated to occur at a pressure around 17 GPa, and the accepted hardness is considerably lower than this value. Jasinevicius and Pizani have shown [23] that semiconductors may present a totally different response to machining based upon the difference between indentation hardness of the pristine crystal and the transition pressure value. According to the authors, InSb (Hv ; 2.3 GPa) presents a larger plasticity than GaAs (Hv ; 6.9 GPa) and Si (Hv ; 11-12.5 GPa).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the geometrical aspects described above, another parameter which affects the brittle-to-ductile transition is the rake angle, together with the material's pressure-induced phase transformation. The use of highly negative rake angles for ductile machining has proved its efficiency in ductile mode diamond turning tests of silicon wafers and other II-VI semiconductors crystals [21][22][23]. This is relevant once Fresnel lenses' fabrication demands the prevention of brittle damage to the edges of the zone steps [25].…”
Section: Machining Planmentioning
confidence: 99%
“…It has been proposed that the critical thickness of cut for these materials varies with the transition pressure value of each crystal [22]. The higher the value of the transition pressure, the lower the critical thickness of cut [23]. The application of a deterministic material removal process to generate rotational diffraction optical elements in semiconductor crystals has recently been tried [24][25][26].…”
Section: Introductionmentioning
confidence: 99%